Behavioural analysis of manta ray tourists in Eastern Indonesia. (April 2019) - Hani, M S; Jompa, J; Nessa, M N; White, A T
Abstract: Indonesia has several manta ray aggregation sites, including Nusa Penida, Komodo, and Raja Ampat. The popularity of manta ray watching tourism has attracted tourists to Indonesia from around the world. Understanding tourist behaviour is vital in order to develop operational approaches and strategies for species protection and tourist satisfaction. The objectives of this study were to analyse tourist motivation, attitudes, preferences, and perceptions before, during, and after manta ray watching. Questionnaires were distributed during May-June 2018, involving 20 local operators and 43 respondents. The traveling patterns of manta tourists indicate that they rarely travel alone, most prefer 1-3 companions; they generally spent several days in the destination area, used a variety of lodging options, and selected nature as the primary reason for their visit. In Nusa Penida and Komodo, most tourists decided to go manta ray watching after arriving at their destination, in contrast to Raja Ampat. They spent a minimum of 500 and up to more than 1000 (excluding airfares). The Likert scale analysis shows three main factors affecting tourists' decision to go manta ray watching: to see manta rays in their habitat; to view an endangered species; and to interact with the fish. Specific attitudes and behaviours of manta ray tourists included: viewing manta rays from a distance; diving, and snorkelling encounters; visiting several manta locations; willingness to pay extra for species conservation; revisiting specific locations; following procedures/code of conduct. Favourite aspects enjoyed by tourists were manta ray morphology and swimming behaviour.